Studies of the Accelerating Effect of Thiourea on the Reduction of Zn in Mixed Water–Organic Solvents at the Mercury Electrode - B. Marczewska (Adsorption Science & Technology)
The accelerating influence of thiourea on the Zn II /Zn(Hg) reduction process was investigated in the following mixed solutions: water–methanol (MeOH); water–ethanol (EtOH); water–dimethyl sulphoxide (DMSO); water–dimethylformamide (DMF). It was suggested that the dominant role in acceleration of the electrode process is played by the composition of the activated complex, which is presumably composed of solvent molecules and thiourea molecules adsorbed on to the electrode. A mechanism was proposed for the process occurring.